Patterns of Power Relation of Street Vendors in Bandung City - Hermawati, Rina; Paskarina, Caroline (Political Science Program, Universitas Negeri Semarang, 2020)
This article discusses how power relation run in daily life and how they relate in governing public issue within multi-stakeholders’ context. The setting of this relations is in the governance of street vendors in Bandung City. Street vendors is usually perceived as problem for urban governance, not only for public convenience and order, but also as spatial or territorial contestation among various actors, namely street vendors, the City Government of Bandung, and the public. In this spatial contestation, there is a power relation that connects various interests and demonstrates the network pattern of actors in fighting for their interests. This article is purposed for mapping of street vendor’s power relation pattern. By mapping the pattern of power relation, it is expected that the handling of street vendors can be more substantive in addressing the source of the problem, and it does not just focus on the eviction on the surface. This research used qualitative method. Data collection technique contains participative observation, through interview with street vendors, city government officials, street vendors association, and focus group discussion. The research result found three patterns of power relation in governing street vendors. The first pattern, street vendors use the association of street vendors as the mediator in negotiating the problem they face. The second pattern, street vendors use the local community of street vendors as the mediator. The third pattern, street vendors use non-governmental organizations (NGOs) as the mediator.